RUANG LINGKUP SISTEM INFORMASI PENDIDIKAN DALAM LEMBAGA PENDIDIKAN - Akhmad Zaenul Ibad (Promis, 2022)
The purpose of this study is to know and understand how a good educational information system to be implemented in educational institutions. The methodology used in this study is a literature study by collecting data in the form of the results of previous research then analyzed and reinterpreted. The object of this study is a temporary information system that is the subject of this study is an educational institution. Based on the discussion, it can be seen that the information system in educational institutions is very important in supporting the implementation of effective and efficient educational activities and activities in the midst of technological and information developments that are rapidly changing and experiencing development. Keywords: System, Information, Education, Educational Institutions